Situation Report: Hungary, 18 December 1973 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Powerful New Transmitters to Improve Radio Reception Sale of Kennedy Rings, US Army Insignia, and Sheriff's Stars Prohibited Problems of Rural Youth Circle of Young Writers Created Tourism: More Profitable than Export? The Tourist Sector: 1974 Swedish-Hungarian Trade Relations Final Accounts Being Drawn up in Agricultural Co-Operatives Frigyes Puja New Foreign Minister